Manage your life with Outlook for dummies - Harvey, Greg (--For dummies., 2008)
An all-new guide that unlocks the secrets of greater Office 2007 productivity-a must-have for power users and everyone who would like to work more efficientlyOffers scores of tips, tricks, and techniques to boost productivity with the programs people use every day-Word, Outlook, Excel, and PowerPointTopics covered include dealing effectively with e-mail, effectively managing files, using and creating templates, reusing and remixing content, sharing and reviewing content, and efficiently managing time and schedulingThe CD-ROM and companion Web site offer podcasts of key productivity tips from t.